SAKINAH DI ERA MODERN: INTEGRASI PERSPEKTIF ISLAM DAN PSIKOLOGI DALAM RELASI PASUTRI - Khairun Nisa; Taufik Hidayat (PT. Sulthan Journal Publisher, 2025)
Marriage in the modern era faces complex challenges, ranging from shifts in gender roles to psychological pressure resulting from digitalization. This study aims to examine the concept of marriage in Islam as a psychological and spiritual institution, as well as to analyze how the integration of Islamic values and family psychology approaches can build healthy husband-wife relationships. The research method used is qualitative with a library research type through an integrative approach that connects normative-religious literature with family psychology theories. The results of the study show that the concepts of sakinah, mawaddah, and rahmah in Islam directly intersect with emotional well-being and interaction stability in family psychology. This integration positions the principle of musyawarah (consultation) as a form of assertive communication and the principle of ishlâh (reconciliation) as a collaborative conflict resolution strategy. These findings conclude that combining the spiritual dimension, involving worship and ethical awareness, with the psychological dimension, such as attachment and emotional regulation, is able to strengthen family resilience in facing the challenges of individualistic modern society.